Vibration Characteristics of Gravity-Type Caisson Breakwater Structure with Water-Level Variation. (26th November 2013) - Lee, So-Young; Huynh, Thanh-Canh; Kim, Jeong-Tae; Yoon, Han-Sam; Han, Sang-Hun
Vibration characteristics of gravity-type caisson breakwater structures which have water-level variations are experimentally examined by using wave load excitations. To achieve the objective, the following approaches are implemented. Firstly, vibration analysis methods are selected to examine the dynamic characteristics of the lab-scale caisson. Secondly, vibration test on a lab-scale caisson which is installed in a two-dimensional wave flume is performed under several excitation sources and water levels. Thirdly, the compatibility of the wave-induced vibration responses is evaluated by comparison with the impact vibration responses, and the appropriate vibration analysis method is selected. Finally, the water-level effects on the caisson breakwater are examined based on the modal parameters which are experimentally measured for the 2D wave flume tests.